NOTARY'S RESPONSIBILITY FOR THE DEED HE MADE IN DECISION NUMBER 126/PDT/2018/PT YYK - BAGAS JUNIO PRIDASMARA (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2023)
In executing his duties as a Public Official, a Notary must comply with the Notarial Office Regulations, the Code of Ethics, and also with the oath taken when appointed as a Notary, where the Notary is obliged to carry out his duties with trustworthiness, honesty, diligence, independence, and impartiality as stipulated in Article 4 paragraph (2) of the Notary Law. However, in Decision Number 126/PDT/2018/PT YYK, the Notary did not comply with these rules. The formulation of the problem in this study is: (1) What is the responsibility of the Notary for the deeds he made based on Decision Number 126/PDT/2018/PT YYK? (2) What are the legal consequences of the deeds made by the Notary based on Decision Number 126/PDT/2018/PT YYK? The research conducted uses normative juridical research with a legislative approach. The legal material collection technique is through literature study. The legal materials used are primary, secondary, and tertiary legal materials. Based on the research results, the Notary who made the deed in case Number 126/PDT/2018/PT YYK did not adequately apply the principle of caution, causing one of the parties to suffer losses, and the results of the second research on the legal consequences of the Notary's deed should be revoked, but the judge has a different opinion.Keywords: Notary’s Responsibilities; Authentic Deed.